The Effect of Mathematical Habits of Mind and Early Mathematical Ability on Modeling Ability of High School Students - Aprilia, Almyra; Asih, Endang Cahya Mulyaning; Usdiyana, Dian (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Modeling mathematics serves as a bridge between the processes of translating real-world problems into mathematics. In reality, however, students' mathematical modeling skills, including their knowledge of derivative applications, remain subpar. This study is intended to determine the relationship between mathematical modeling skills, mathematical habits of mind (MHoM), and early mathematical ability (EMA). This research employed a quantitative methodology with mix method sequential explanatory design. The method used a quantitative and qualitative approach. The first quantitative phase is used, then explained more deeply through the qualitative phase. Sample in this study were 36 eleventh-grade students from one of Tasikmalaya's senior high schools. In this investigation, the EMA was the previous semester's math report card grade. A mathematical modeling ability test question and an MHoM questionnaire were administered to students, and the quantitative analysis of the results followed. This study demonstrates that the relationship between MHoM and EMA has a 31.2% modeling capability. In addition, a one-point increase in MHoM and EMA increases the average mathematical modeling ability of pupils by 1,570 and 2,241. Therefore, it can be concluded that MHoM and EMA have a positive effect on mathematical modeling ability.